Desenvolvimento, perícia e poder no rural paulista : o caso do Programa Estadual de Microbacias Hidrográficas - Gameiro, Mariana Bombo Perozzi (2013)
This research analyzes the relations established by agents with the expert knowledge in the context of a public policy for rural development, by reconstructing the experiences of those who took part of its processes of formulation and implementation. These processes are often mediated by funding institutions and rural extension agencies. Analyzing social phenomena from the perspective of mediations, and more specifically, from the perspective of expertise, assumes the centrality of power dimensions, the identification of its asymmetries and constant disputes over the construction of views about ruralities. The object of this study is the Land Management III Project (Programa Estadual de Microbacias de São Paulo - PEMH), one of the first public policies with a territorial, decentralized and participative approach for the sustainable rural development of the State of Sao Paulo. This program was partially financed by the World Bank and executed between 2000 and 2008 by the State Secretary of Agriculture, through its rural extension body, the Coordination of Integral Technical Assistance (CATI). The problematization of this research was designed from Anthony Giddens concept of systems experts, from whom we also extracted the notions of reflexivity, agency, time and space. Manuel Castells concepts of space of flows and space of places also assisted in the interpretation, as well as Michel Foucault's formulations on discourse. The field researches required the contributions of Luc Boltanski and Erving Goffman on trust and interaction processes. Techniques of social qualitative research, such as interviews and document analysis, were employed.